Leiomyoma as a lead point for small bowel intussusception in a 16-year-old - Stephanie N. Williams; Morris Edelman; Barrie S. Rich (Elsevier, 2022)
Intussusception is a common gastrointestinal phenomenon in the pediatric population. While it typically affects the ileocolic region, the small bowel may also be affected. Intussusception that occurs outside of the small bowel typically requires radiographic or surgical intervention, however, small bowel intussusception (SBI) usually self-resolves without the need for any intervention. We describe a case of a 16-year-old boy who required an emergent small bowel resection for a SBI with resultant necrotic bowel. He was found to have a leiomyoma as a lead point. We go on to review the literature on this rare finding in the pediatric population.